Intensitas Aktiva Tetap, Kompensasi Eksekutif, Kepemilikan Institusional dan Tax Avoidance - Sarasmita, Luh Pringgita Tami; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 31 No 10 (2021), 2021)
This study aims to obtain empirical evidence regardingthe effect of fixed asset intensity, excecutive compensation, and institusional ownership on tax avoidance in the Mining Sector Manufactur contained on the Stock Exchange in the 2016-2019. The sample was determained using the nonprobability sampling method with a purposive sampling technique, obtained as many as 55 companies with 4 of observation in order to obtain 220 data observations. Data analysis techniques using the Multiple Liniear Regression test. The sampling method used is purposive sampling. Data analysis techniques using the Multiple Linear Regression test. The results of this study indicate that the intensity of fixed assets and institutional ownership has a negative effect on tax avoidance. This means that the higher the intensity of the company's fixed assets and the greater the company's institutional ownership causes the lower level of tax avoidance. Executive compensation has a positive effect on tax avoidance. This means that the higher the compensation given to the executive, the higher the level of tax avoidance. Keywords: Fixed Asset Intensity; Excecutive Compensation; Institusional Ownership; Tax Avoidance.